Development of a symbolic image of building structure in CAD - Stanovskyi, Alexandr; Abu Shena, Osama; Toropenko, Oleksii; Daderko, Olesya (Technology audit and production reserves, 2017)
The object of research are the processes of automated design of construction or reconstruction of complex building structures under the conditions of individual restrictions on each structure - technical heredity caused by internal and external environment surrounding construction. One of the problematic areas of automated construction design is due to the fact that it constantly needs to restore the model of the structure. This model should reflect not only the primary technical design for the building (drawings, etc.), but also found when designing the changes and developments in the turbulent internal and external environment surrounding the future construction environment. As a result of the analysis of the role of the terms of reference and its place in the process of automated design of building structures, it is established that the initial task must be constantly adapted to the external and internal environment of the building. On the other hand, it must also adapt to the conditions that the particular building has inherited from its predecessors or neighbors. It is proposed to use models known as the complex genetic algorithm in the form of branched chromosomes as symbolic models of building constructions, and the accumulation of «same-sex mutations» in them to simulate ossification (prohibition of change) in any transformation of the corresponding genes. The results of the work in the form of CAD «TEHED» are involved in the reorganization of the facade of an industrial facility in order to increase its ventilation, energy-saving and lighting characteristics. The tests show that the use of CAD «TEHED» allows to reduce the terms of automated design of reconstruction by 23.4 %, as a result, the cost of reconstruction was 18.9 % lower than planned.